Aboriginal Wingadhan Birrang (woman's journey) of smoking cessation during pregnancy as they participate in the ICAN QUIT in pregnancy pilot step-wedge trial. Issue 3 (May 2020) - Bovill, Michelle; Bar-Zeev, Yael; Bonevski, Billie; Gruppetta, Maree; Oldmeadow, Chris; Hall, Alix; Reath, Jennifer; Gould, Gillian S.; ,
Abstract: Background: Addressing smoking cessation during pregnancy among Aboriginal women is a national priority under the Closing the Gap campaign. There is a need to measure and report interventions to support Aboriginal women during pregnancy. Aim: To quantitatively assess women's smoking experiences over a 12 week ICAN QUIT in Pregnancy program. Methods: Aboriginal women and/or women expecting an Aboriginal baby reported their smoking experiences through repeated cross-sectional survey at baseline, four weeks, and 12 weeks. Self-reported nicotine dependence measures (heaviness of smoking index, strength of urges and frequency of urges to smoke), intentions to quit smoking, quit attempts, use of nicotine replacement therapy were gathered as well as a carbon-monoxide measure at each time point. Results: Expectant mothers (n = 22) of Aboriginal babies participated from six Aboriginal Community Controlled Health Services between November 2016 and July 2017. At 12 weeks women reported (n = 17) low heaviness of smoking index 1.21 with high strength of urges 2.64 and frequency of urges 3.00; 12/13 (92%) reported likely/very likely to quit smoking, made a mean 1.67 number of quit attempts, three women (13.6%) quit smoking (validated); 5/16 (31%) reported using nicotine replacement therapy. Discussion: Participating women made multiple quit attempts demonstrating motivation to quit smoking. Smoking cessation interventions should be tailored to address high strength and frequency of nicotine dependence despite low consumption. Conclusion: Prolonged smoking cessation support is recommended to address physical, behavioural and psychological aspect of smoking. Cessation support should address previous quitting experiences to assess smoking dependence and tailoring of support. Trial registration: Australian and New Zealand Clinicial Trials Registry (Ref #ACTRN12616001603404).